The wedding planner [compact disc, unabridged] - Steel, Danielle (Recorded Books, Inc., 2023)
After two failed engagements, Faith Ferguson, New York's most popular wedding planner, has no desire to get married herself. Through her own journey, Faith will prove once and for all that that there is not just one path to happily ever after.